Strategi Dakwah Pesantren dalam Mengwujudkan Masyarakat yang Harmonis: Studi Pesantren Kec. Suka Makmue, Kab. Nagan Raya, Aceh - Ajidan Ajidan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
This research is used to know the strategy used in realizing harmonious society, by using research sample of Pesantren Babul Hidayatil Muslim, Nurul Huda, and Darul Aman. The three pesantren are located in Suka Makmue sub-district, Nagan Raya District, Aceh Province. Judging from the problems that arise today, that some non-formal education is no longer used as role models in society, but in this case researchers are interested to examine the three pesantren are still a light for the community and have a very significant influence. The strategy used is very simple but it brings the effect that sasy is terrible, such as communicating with maui'zatul hasanah ie in a gentle way and do not force the will of society. Apart from that the participation of the pesantren in community events, such as kenduri, and so forth. Although the challenges faced are quite large but it all does not affect the effort to form a harmonious society to hear the basis of sincerity without expecting a reward for the efforts it undertakes.